Determination of Cyanide in Amanitia muscaria Samples Using Alkaline Picrate Method - Nwokoro, O.; Ogbonna, J.C.; Ubani, C.S.; Okpala, G.N.; Ofodile, O.E. (Pakistan Journal of Nutrition, 2010)
Analytical methods were developed for the detection of cyanide in Amanitia muscaria samples using the alkaline picrate method. Dried mushroom samples contained in glass bottles were treated with acid solution and maintained at 80oC for 10 min. Hydrogen cyanide vapours librated from the samples reacted with alkaline picrate solution on Whatman filter paper strips to form red-coloured complex on the test strips. The red coloured compound on the test strips were extracted with 50% ethanol solution and the extract absorbance read at 510 nm. A linear relationship was obtained between the ranges of 0-200 μg CN. Cyanide was detected in mushroom samples at the levels of 84-712 μg/10 g sample. Recovery of cyanide from the samples demonstrated that cyanide poisoning could occur in populations due to prolonged intake of toxigenic mushroom samples. Association between cyanide intake from cyanogenic mushroom and the manifestation of severe human diseases were discussed.